Web Services, Formal Methods, and Behavioral Types : 11th International Workshop, WS-FM 2014, Eindhoven, the Netherlands, September 11-12, 2014, and 12th International Workshop, WS-FM/BEAT 2015, Madrid, Spain, September 4-5, 2015, Revised Selected Papers /: 11th International Workshop, WS-FM 2014, Eindhoven, the Netherlands, September 11-12, 2014, and 12th International Workshop, WS-FM/BEAT 2015, Madrid, Spain, September 4-5, 2015, Revised Selected Papers. (2016) - Unknown
No abstract available